Porous reduced graphene oxide paper as a binder-free electrode for high-performance supercapacitors. Issue 34 (15th April 2015) - Liu, Yu; Ying, Yulong; Mao, Yiyin; Hu, Pan; Peng, Xinsheng
<x xml:space="preserve">Abstract</x> Porous rGO exhibited an excellent high specific capacity of 173.5 F g−1, good cycling stability, and 28.5 W h kg−1 and power density of 4000 W kg−1, far beyond those of pure stacked rGO paper.